PEMANFAATAN HISTORY PADA BROWSER KOMPUTER UNTUK MENENTUKAN PEMILIHAN WEBSITE ATAU BLOG PADA SEOINDONESIA - Ketut Agus Adi Arlina; Yenni Astuti (Compiler, 2014)
Seoindonesia is a web based application that is used to boost the ratings visitors of website or blog using Together in Single Connection (TSC) technique. In this software, the selection of blogs or websites that would be raised using a lowest ratings pattern. Website or blogs listed on Seoindonesia opened by random with choosing some websites or blogs that has the lowest ratings. The selection of a websites or blogs randomly, causing discomfort to the user side. One way to access and improve seoindonesia is to use history on the browser. History on the browser is a facility to record and store data of story browsing and use of the internet search history. Utilization history on browser can only be accessed by using the extension. Extensions is a plug-in applications that have a specific function and can be installed on a computer's browser. Web browser noted most frequently visited of history or blog and than sent to the extensions can be used to direct the opening of a new website or blog address in accordance with the categories of the previous website address. Website or a blogsposted by extension,is a member of seoindonesia, so it can increase the number of visitors who will rise the rank, with an increase of 64% (7 points) and 36% (4 points) decreased with the overall function of the test is 11 points in seo alexa rank.Application development by using a browser on computer,able to improve the system seoindonesia on the grouping and categorizing of website or blog.